Alcohol Consumption Reduction and Clinical Outcomes of Catheter Ablation for Atrial Fibrillation - Takahashi, Yoshihide; Nitta, Junichi; Kobori, Atsushi; Sakamoto, Yuichiro; Nagata, Yasutoshi; Tanimoto, Kojiro; Matsuo, Seiichiro; Yamane, Teiichi; Morita, Norishige; Satomi, Kazuhiro; Inaba, Osamu; Murata, Kazuya; et al. (Circulation. Arrhythmia and electrophysiology, 2021)
[Figure: see text].